The role of social media as a communication facility for hydrometeorological disasters in shallot farming activities - Nurul Khotimah; Dyah Respati Suryo Sumunar; Suhadi Purwantara; Nugraho Sistu Prabintoro; Mohd Hairy Ibrahim; Nasir Nayan (Universitas Negeri Yogyakarta, 2022)
Social media as a means of communication plays a role in building a new paradigm of disaster. One of the social media users for hydrometeorological disaster communication is a shallot farmer in Parangtritis Village, Kretek Subdistrict, Bantul District, Yogyakarta Special Region. This study aims to determine the role of social media as a means of communication for hydrometeorological disasters in shallot farming activities. The design of this research is descriptive quantitative research. The research was carried out from April to October 2021 by taking the location of shallot farmers in Parangtritis Village, Kretek Subdistrict, Bantul District, Yogyakarta Special Region. The research sample was determined by a quota of 50 respondents. Research data were collected through observation, interviews, and documentation. The data that has been collected is then processed and analyzed descriptively. The results of this study show that: (1) The respondents' ownership of gadgets is 84%. Of all respondents who have gadgets, 71.4% of respondents have an internet connection. (2) All respondents stated that ownership of gadgets and internet connection is useful in hydrometeorological disaster information. (3) All respondents who have gadgets and internet connections have facebook and whatsapp social media accounts. (4) The role of ownership of social media accounts is as a means of exchanging information on hydrometeorological disasters, namely information related to shallot farming activities (seedlings, soil processing, fertilizers, pest eradication, harvesting, etc.) and information on the threat of hydrometeorological disasters on shallot farming, such as floods and extreme weather. The existence of social media is able to have a positive impact on shallot farmers, especially in adapting to existing weather conditions with strategies to change crop variations, change cropping patterns, change planting periods, and change irrigation systems, thereby helping harvest success.